The development of indicators for utilising portable electronic devices of the undergraduates - Damrongpanit S. (2017)
© Medwell Journals, 2016. There are 3 objectives in this research. To study students' behaviours for utilising portable electronic devices. To integrate the indicators and factors of the use of portable electronic devices and to validate the measurement structure of the use of portable electronic devices. The sample groups were 282 students in the Faculty of Education, Chiang Mai University. The research Instruments were the questionnaires with 25 questions. The discrimination values were between 0.182-0.661. The reliability value was equal to (α) 0.862. The data analysis used the descriptive statistics and factors analysis. The findings revealed that there were 25 indicators of utilisation and could be divided into 2 dimensions including daily life total 11 indicators and learning total 14 indicators. The most popular device was a Smart Phone (93.15%), there were 4 factors of the daily life aspect which were online payment, picture and sound, relax and remind and movies and social. The learning also had 4 factors consisting of homework and notice, remind and storage, technical supports and telecommunication and the measurement structure of utilisation showed the validity value at the good level.